POLA PENGGUNAAN ANTIBIOTIK PADA PASIEN PNEUMONIA RAWAT INAP DI RSUD dr. GONDO SUWARNO TAHUN 2021 - Iswandi Iswandi (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2022)
Pneumonia is an infection at the ends of the bronchioles and alveoli which causes acute inflammation of the lung parenchyma caused by various pathogens such as bacteria, fungi, viruses and parasites. Most are caused by bacteria. Inappropriate use of antibiotics can lead to increased resistance, wasted costs and does not achieve optimal clinical benefits in the prevention and treatment of infections and bacterial resistance to drugs. The purpose of this study was to determine the suitability of the use of antibiotics according to therapy with the American Thoracic Society/Infectious Diseases Society of America (ATS/IDSA) guidelines. This research method is a type of descriptive non-experimental research with a retrospective approach using cross sectional. Data collection according to the prescription of inpatients at dr. Gondo Suwarno who received antibiotics. Then grouped by type of antibiotic, dose, class, and duration of antibiotic administration. The number of samples is 100. Then the data is adjusted between therapy and guidelines. Based on the results of the study, it was found that there were more male patients. The most widely used dosage form is injection. The most common class of antibiotics is the cephalosporin group. In CAP pneumonia, the number of patients was 46 with the accuracy of the type of drug levofloxacin as many as 12 (26.08%). In HAP pneumonia, the number of patients was 54, with the accuracy of the type of antibiotic levofloxacin in 16 (29.62%). The accuracy of the type of ceftriaxone drug was 22 (40.74%)